Pulling on Super Paramagnetic Beads with Micro Cantilevers: Single Molecule Mechanical Assay Application - Melo-Hurtado, F; Aguilar-Sandoval, F; Muñoz-Buzeta, R (Institute of Physics Publishing, 2015)
This paper demonstrates that it is possible to trap and release a super paramagnetic micro bead by fixing three super paramagnetic micro beads in a triangular array at the sensitive end of a micro cantilever, and by simply switching on/off an external magnetic field. To provide evidence of this principlewetrapamicro bead that isattached tothe free end of single DNA molecule and that has been previously fixed at the other end to a glass surface, using the standard sample preparation protocol of magnetic tweezers assays. The switching process is reversible which preserves the integrity of the tethered molecule, and a local force applied over the tethered bead excludes the neighbouring beads from the magnetic trap. We have developed aquadrature phase interferometer whichis able to perform under fluid environmentsto accurately measure small deflections, which permits the exploration of DNA elasticity. Our results agree with measurements from magnetic tweezer assays performed under similar conditions. Furthermore, compared tothe magnetic tweezer methodology, the combination of the magnetic trap witha suitable measurement system for cantilever deflection, allows for the explorationofawide range offorces using alocal method that hasanimproved temporal resolution. © 2015 IOP Publishing Ltd.